The Influence of Teacher Competence, Classroom Management, and School Infrastructure on the Learning Quality of Islamic Religious Education (PAI) (Study in Class IX of SMP Islam 1 Batu) - Yeni Endiana; Munirul Abidin; Adam Saad Ahmed Ali (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2026)
Limited research has simultaneously examined the influence of teacher competence, classroom management, and school infrastructure on the quality of Islamic Religious Education (PAI) learning, despite the recognized importance of these components in supporting effective instructional processes. This study aims to analyze the partial and simultaneous influence of teacher competence, classroom management, and school infrastructure on the quality of PAI learning. The study employed a quantitative approach involving 60 participants selected through saturated sampling, in which all members of the population were included as the research sample. Data were collected using questionnaire-based research instruments and analyzed through multiple linear regression. The findings show that classroom management had the dominant influence on the quality of PAI learning, thereby supporting the relevant theoretical perspective. The partial test results indicate that teacher competence and school infrastructure did not have a significant effect on the quality of PAI learning when examined separately. However, teacher competence, classroom management, and school infrastructure simultaneously had a significant influence on learning quality. These findings indicate that the quality of PAI learning is shaped by the combined contribution of teacher-related, classroom-based, and infrastructural factors, with classroom management serving as the most influential variable. This study contributes theoretically by enriching the literature on factors affecting learning quality and provides practical implications for schools and teachers to strengthen effective classroom management, develop teacher competence sustainably, and optimize the use of facilities and infrastructure to support the learning process. Further research is recommended to examine other factors that may influence the quality of Islamic Religious Education learning.